Implementation of Active, Creative, Effective Learning, And Fun In Improving Results of Learning Mathematics Three-Dimensional Concepts - Rifka Andini; Haris Maulana (Indo-MathEdu Intellectuals Journal, 2021)
This research is backgrounded because of the lack of mathematics teachers in applying learning methods that are in accordance with the characteristics of students and the material to be taught so that it affects learning outcomes in the classroom. The purpose of this study is for the implementation of Active, Creative, Effective, and Fun Learning in improving student learning outcomes in class X SMAS PGRI Bolo. The type of research used is Classroom Action Research which consists of four stages, namely action planning, action implementation, obervation and reflection with a total of 25 subjects. The data collection technique is by conducting tests and observations. Observation is carried out by an observer to observe the learning activities of teachers and students and the test is used to find out the learning outcomes of students after participating in learning activities. After analyzing the data on learning outcomes, it was obtained that the average score of students increased, namely in the initial test obtained an average score of 51.52 with a percentage of completion of 28.00 percent, increased in cycle I to 68.24 with a percentage of completion of 60.00 percent and increased significantly in cycle II to 80.16 with a percentage of completion of 92.00 percent